IMPROVING THE STUDENTS’ VOCABULARY MASTERY THROUGH WORD SQUARE GAME AT THE EIGHTH GRADE OF SMP DWIJENDRA DENPASAR IN THE ACADEMIC YEAR 2019/2020 - Maria Ode Berta; Ni Wayan Swarniti (Widyasrama, 2020)
The aim of this research was to know the process of improve the students’ vocabulary mastery through word square game for eighth grade stuxdents of SMP Dwijendra Denpasar in the academic year 2019/2020. The subject was the students of VIII D in the academic year 2019/2020. This class consists of 30 students. In collecting the data, the researcher used test. The test were given in pre-test, post-test 1 and post-test 2. The researcher analyzed the mean score of each test to find out the improvement of students’ vocabulary mastery after the action was conducted. The researcher conducted the action the students’ vocabulary mastery increased optimally. It could be seen from the score that pre-test was 61,55, post-test 1 was 71,03, and post-test 2 was 80. After apply the action the researcher was able to solve the problem in improve vocabulary mastery. The students were able to take the word meaning based on the context. The use of word square game in teaching vocabulary, students could easly understand and memorize new vocabulary. In the teaching process, when the teacher used word square game, the students were enthusiastic and enjoy during teaching learning process.